Designing, developing and evaluating professional language and intercultural competencies with phone simulations. - Gabarre, Cecile; Gabarre, Serge (IGI Global, 2012)
With the development of call centers to handle customer services, many tour operators have adopted the technique of recruitment by simulation where the candidates are judged on their ability to respond to working scenarios. To facilitate the school-to-work transition, we sought to increase the learners’ exposure to professional tasks and to challenge their communication skills in real situations. This chapter specifically relates to the design, implementation and assessment of a phone conversation simulation introduced in the evaluation scheme within the French for Tourism and Hospitality course. The 22 participants were Malaysian learners majoring in French. The analysis of examination results, phone conversation recordings as well as surveys on the learners’ perceptions of the new evaluation format provided a complete feedback on the experience. This chapter aims to present practitioners with a reference guide with step by step explanations and solutions easily transferable to any course with a communication component.